Oncogene Expression Modulation in Cancer Cell Lines by DNA G-Quadruplex-Interactive Small Molecules - Francisco, Ana P.; Paulo, Alexandra (Current Medicinal Chemistry, 2017)
Nucleic acids are prone to structural polymorphism and a number of structures may be formed in addition to the well-known DNA double helix. Among these is a family of nucleic acid four-stranded structures known as G-quadruplexes (G4). These quadruplex structures can be formed by sequences containing repetitive guanine-rich tracks and the analysis of Non-B-DNA database indicated an enrichment of these sequences in genomic regions controlling cellular proliferation, such as for example in the promoter regions of c- MYC, k-RAS, c-KIT, HSP90 and VEGF among others. The broad concept of G4 targeting with small molecules is now generally accepted as a promising novel approach to anticancer therapy and several small molecules with antiproliferative activity in cancer cell lines have also been shown to stabilize these DNA structures, thus suggesting a potential application of G4-interactive small molecules as new anticancer drugs. Herein we review, by targeted oncogene and main chemical scaffold, those G4-interactive small molecules with reported gene expression modulatory activity in cancer cell lines. The data obtained so far are encouraging but further efforts are needed to validate G4 as drug targets and optimize the structure of G4- interactive small molecules into new anticancer drugs.
Keywords: DNA